PEMBELAJARAN QIRA’AH MENGGUNAKAN MEDIA BLOOKET BERBASIS HUMANISTIK - Freti Efrilia; Kristina Imron; Irmansyah (El-Tsaqafah : Jurnal Jurusan PBA, 2026)
This study aims to develop qirā’ah material using Blooket media based on a humanistic approach for eighth-grade students of Ar-Risalah Junior High School, Lubuk Linggau, and to test its effectiveness in Arabic language learning. The background of this study is based on students' low understanding of Arabic reading texts due to the use of less interactive learning materials and media and a learning approach that is still teacher-oriented. This study uses the Research and Development (R&D) method with the ADDIE model which includes stages, design analysis, development, implementation, and evaluation. The product developed is qirā’ah material in the form of an educational game on the Blooket platform designed based on humanistic learning principles. The research subjects were eighth-grade students of Ar-Risalah Junior High School, Lubuk Linggau. Data collection techniques included observation, interviews, questionnaires, and learning outcome tests. The results showed that the qirā’ah material based on Blooket media was declared valid and suitable for use based on the assessment of material experts and media experts. In addition, the use of humanistic-based Blooket media was proven effective in improving students' reading comprehension, learning motivation, and active participation in Arabic language learning. Thus, the development of qirā’ah material using humanistic-based Blooket media can be an innovative alternative in Arabic language learning at the junior high school level